How to do things with examples: Sufis, dreams, and anthropology. (May 2015) - Mittermaier, Amira; BANDAK, ANDREAS; HØJER, LARS
<x xml:space="preserve">Abstract</x> In this paper I explore how members of a Sufi community in Egypt use dream‐stories as examples to evoke an otherwise invisible realm, and how I, in turn, use their stories ethnographically. My Sufi interlocutors use examples to invite others into the realm of the imagination, to draw listeners into the shaykh's spiritual aura, and to offer a model for emulation that sometimes triggers similar experiences in others. Their approach to examples poses a challenge to the logic of representation, in which a particular stands in for a larger whole. Instead it points to an evocative logic in which examples do not merely represent; they also do things. Whereas ethnographic examples tend to oscillate between representation and evocation, referential language ideologies largely obscure the example's evocative power. I suggest that my interlocutors' use of, and approach to, examples can help us think about the example as evocative and performative, including the ways in which examples act upon and through anthropologists.